2017
DOI: 10.1080/09638288.2017.1402095
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ needs during a surgical intervention process for Dupuytren’s disease

Abstract: Clients' needs during a surgical intervention process include needs for improvement of hand function, knowledge, and support during treatment, and participation in evaluation. Clients' needs change during the care process and can be influenced by their life situation or their character. The identified needs ought to be included in quality assessments from the carers' perspective, to ensure that important needs of the clients are met by the surgical intervention process. Communication and interaction between cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Comparative studies have shown that hand function and low recurrence rates following an operation are vital aspects of care to patients. 8,17 We, therefore, advocate an approach where early wound care and introduction of hand therapy are key tenets of postoperative care to optimize hand function.…”
Section: Discussionmentioning
confidence: 99%
“…Comparative studies have shown that hand function and low recurrence rates following an operation are vital aspects of care to patients. 8,17 We, therefore, advocate an approach where early wound care and introduction of hand therapy are key tenets of postoperative care to optimize hand function.…”
Section: Discussionmentioning
confidence: 99%
“…The patients' life situation, life history and patient character also influence patients' evaluation of care and results (23). Two articles have been published previously with the objectives of describing clients' experiences of care, needs, expectations, and appraisal of results during a surgical intervention process for DD (19,31). This article focuses on the phase pre-admission and patients' experience and significance of illness.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, Thoma et al (2014) reported on health-related quality of life 12 months after surgery. Two qualitative studies also reported the patient perspective, including a need for treatment to result in an improved ability to return to activities that were important to them and increased knowledge about the condition and treatment options (Turesson et al, 2019;Molineux et al, 2022). One study also highlighted the carer's perspective as essential when measuring the quality of the surgical intervention process (Turesson et al, 2019).…”
Section: Professionals' Perspectives Prioritisedmentioning
confidence: 99%
“…Two qualitative studies also reported the patient perspective, including a need for treatment to result in an improved ability to return to activities that were important to them and increased knowledge about the condition and treatment options (Turesson et al, 2019;Molineux et al, 2022). One study also highlighted the carer's perspective as essential when measuring the quality of the surgical intervention process (Turesson et al, 2019). Additionally, a focus on health literacy as essential to patient recovery, satisfaction with treatment and wellbeing was included in more recent publications (Molineux et al, 2022;Russell, 2022;Winberg and Turesson, 2022).…”
Section: Professionals' Perspectives Prioritisedmentioning
confidence: 99%
See 1 more Smart Citation